The Effect of using a Semi-Automatic Foam Cutting Machine on The Characteristics of Foam Patterns in The Lost Foam Casting - Sadegh Mirzamohammadi; Abbas Abbasian; Seyed Jalal Hashemi (International Journal of Advanced Design and Manufacturing Technology)
In this research, a modern method for making foam patterns, which is one of the most important steps of casting with a lost foam pattern, has been used. A semi-automatic hot wire machine was built to cut and create foam patterns. Two types of foam patterns were prepared by manual method and cutting method with semi-automatic machine. The sizes of the obtained foam patterns were evaluated and the accuracy of each method in the production of foam patterns was compared. According to the density of the foam used in the experiments, the volume of the prepared patterns was obtained by manual and semi-automatic methods. The additional volume in the prepared patterns was calculated by both methods. The amount of economic losses caused by excess volumes was investigated. The results of the research determined that the accuracy of the sizes of the patterns prepared by the semi-automatic method was more than twice the accuracy of the patterns prepared by the manual method. The patterns prepared by the semi-automatic method had an additional volume of 1.9% compared to the volume of the original part. While the mentioned amount for foam patterns cut by the manual method was 9%. Therefore, the economic efficiency of casting parts using foam patterns made by semi-automatic method in terms of melting consumption for aluminum parts was 8% more than production parts using foam patterns made by manual method.